Labor migration and commodity production in Africa: global entanglements - (:unkn) unknown (My University, 2024)
This introductory article presents the objectives, scope and contents of the Special Issue titled Labor Migration and Commodity Production in Africa: Global Entanglements. By congregating a diverse team of scholars from Brazil, Turkey, Germany, France, the United States, and Cameroon, all at different stages of their careers, this Special Issue seeks to build upon current trends in the fields of Global and African History to expand our current understanding of the centrality of African subjects in the making of the contemporary, densely globalized yet deeply unequal world. This introduction sets the theoretical framework that guided our call for papers, summarizes the key findings of each article, and situate their individual contributions within the topics related to the agency of African subjects in the creation of increasingly interconnected societies. We argue that the articles in this Special Issue offer a path to further strengthen and expand both fields of African and Global History by incorporating the analysis of understudied sources from diverse linguistic backgrounds, such as Arabic, Turkish, Portuguese and German, as well as legal documents produced by contemporary African states.
Keywords: African Research